2007
DOI: 10.1016/j.nimb.2006.12.130
|View full text |Cite
|
Sign up to set email alerts
|

Sticking coefficient and SIMS of hydrocarbons on fusion relevant plasma-sprayed tungsten surfaces

Abstract: Abstract:In this work we concentrate on the quantification of the sticking coefficient of CD 3 + on fusion relevant plasma-sprayed tungsten (PSW) surfaces in the collision energy range from about 0 up to 100 eV. PSW samples were cut from ASDEX Upgrade tiles and both untreated and electropolished surfaces are investigated. A collision energy, E coll , selected CD 3 + ion beam deposits hydrocarbon layers onto the target surfaces which are ex-situ analysed by Nuclear Reaction Analysis (NRA) via D( 3 He,p) 4 He at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
(11 reference statements)
2
2
0
Order By: Relevance
“…As already mentioned, like in the previous experiment [7] the shape of the ion beam spot is found to be elliptical with an area of approximately 1 Â 1.5 mm 2 by determining the horizontal and vertical distribution function of the deuterium content around the spots exposed to the CD þ 2 beam with NRA using a 3 He beam of 1 Â 1 mm 2 size. By comparing the fluence with the areal density of deuterium, the sticking coefficient of deuterium is found not to show the same dependency on incident energy over the investigated energy range up to 100 eV.…”
Section: Interaction Of D With Carbon Fibre Compositesupporting
confidence: 72%
See 1 more Smart Citation
“…As already mentioned, like in the previous experiment [7] the shape of the ion beam spot is found to be elliptical with an area of approximately 1 Â 1.5 mm 2 by determining the horizontal and vertical distribution function of the deuterium content around the spots exposed to the CD þ 2 beam with NRA using a 3 He beam of 1 Â 1 mm 2 size. By comparing the fluence with the areal density of deuterium, the sticking coefficient of deuterium is found not to show the same dependency on incident energy over the investigated energy range up to 100 eV.…”
Section: Interaction Of D With Carbon Fibre Compositesupporting
confidence: 72%
“…Our first experiment concerning the question of fuel retention by deposition of hydrocarbon ions formed subsequently to impact of deuterium on carbon surfaces in an experimental fusion reactor cladded with vacuum plasma sprayed tungsten coated tiles, showed that electron-polishing of plasma-sprayed tungsten surfaces reduces the magnitude of the sticking coefficient of a hydrocarbon species known for its high adsorption probability, the methyl radical ion CD þ 3 by a factor of about 4 [7]. Our main aim was to quantify the sticking coefficients of the next smaller deuterated hydrocarbon CD þ 2 on untreated PSW and for comparison also on CFC surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…At thermal energies the sticking coefficient depends strongly on the electronic configuration of the hydrocarbon molecules decreasing from sp1 to sp2 and sp3 in reasonable agreement with MD calculations, which predicting sticking coefficients close to 1 at energies above 10 eV. Data for sticking coefficients on realistic plasma-facing materials were presented recently [52] and are further studied in the framework of the EU PWI Task Force.…”
Section: Re-deposition Of Hydrocarbon Radicalssupporting
confidence: 68%
“…While without excitation decomposition of incident CH 4 + molecules starts only at 30 eV, indicating that the whole dissociation energy must be supplied by the surface collision, for high internal excitation sufficient to provide the decomposition energy of 1.8 eV the reemission of CH 4 + decreases monotonically with ion energy. Data for sticking coefficients on realistic plasma-facing materials were presented in this conference [61].…”
Section: Iv-2-b) Re-deposition Of Hydrocarbon Radicalsmentioning
confidence: 99%